Revision of the genus Hemopsis Kirti & Rose, 1987 (Lepidoptera, Crambidae), with descriptions of three new species from China - Cheng-Jun Yu; Xi-Cui Du (ZooKeys)
The genus Hemopsis is revised based on adult morphological characteristics and DNA barcodes. Hemopsis abstracta sp. nov., H. coalita sp. nov., and H. heteroidea sp. nov. are described as new to science, and Hemopsis dissipatalis (Lederer, 1863) is DNA barcoded and redescribed based on new material from southern China. A key to Hemopsis species is given based on external morphology of adults and their genitalia characteristics. Images of adults and genitalia are provided.